Evaluation of ConPrim: A three-part model for continuing education in primary health care. (November 2016) - Berggren, Erika; Strang, Peter; Orrevall, Ylva; Ödlund Olin, Ann; Sandelowsky, Hanna; Törnkvist, Lena
Abstract: Background: To overcome the gap between existing knowledge and the application of this knowledge in practice, a three-part continuing educational model for primary health care professionals (ConPrim) was developed. It includes a web-based program, a practical exercise and a case seminar. Aim: To evaluate professionals' perceptions of the design, pedagogy and adaptation to primary health care of the ConPrim continuing educational model as applied in a subject-specific intervention. Methods: A total of 67 professionals (nurses and physicians) completed a computer-based questionnaire evaluating the model's design, pedagogy and adaptation to primary health care one week after the intervention. Descriptive statistics were used. Results: Over 90% found the design of the web-based program and case seminar attractive; 86% found the design of the practical exercise attractive. The professionals agreed that the time spent on two of the three parts was acceptable. The exception was the practical exercise: 32% did not fully agree. Approximately 90% agreed that the contents of all parts were relevant to their work and promoted interactive and interprofessional learning. In response to the statements about the intervention as whole, approximately 90% agreed that the intervention was suitable to primary health care, that it had increased their competence in the subject area, and that they would be able to use what they had learned in their work. Conclusions: ConPrim is a promising model for continuing educational interventions in primary health care. However, the time spent on the practical exercise should be adjusted and the instructions for the exercise clarified. ConPrim should be tested in other subject-specific interventions and its influence on clinical practice should be evaluated. Highlights: ConPrim is a promising model for designing continuing educational interventions. Instructions for the practical exercise should be improved. ConPrim is ready to be tested in other subject areas.